Level of systems thinking competencies among senior high school students - Lia Zaradiva; Widi Purwianingsih; Amprasto Amprasto; Fuad Mardhatillah (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2025)
Environmental issues are characterized by dynamism and complexity, which challenge traditional problem-solving approaches and demand adherence to sustainability principles. In this context, students need to be equipped with systems thinking competencies to better understand and address environmental problems. Systems thinking encompasses the ability to identify components within a system, understand their interrelationships, and manage uncertainty, diversity, and risks. However, there was a lack of empirical evidence on how secondary students conceptualize and apply systems thinking in real-world environmental contexts. This study aimed to assess the level of systems thinking competencies among senior high school students. The participants were 133 tenth-grade students enrolled in the 2024–2025 academic year in East Aceh. Data were collected using an essay-based test consisting of eight items developed from the systems thinking framework UNESCO. Criterion validity was analyze using Pearson correlation, while the reliability of the instrument was determined through Cronbach’s Alpha (0.79, moderate). Descriptive statistics were used to analyze students’ competencies levels. The results showed that most students were categorized at Level 1 (insufficient) and Level 2 (satisfactory), with a smaller portion at Level 3 (good). No students reached Level 4 (very good). These findings offer preliminary insights into students’ systems thinking abilities and highlight the pressing need for effective educational interventions to strengthen their engagement with sustainable development. Therefore, the results provide a standard for designing targeted interventions aimed at advancing sustainable education.Abstrak. Isu-isu lingkungan yang terus berkembang menuntut penanganan yang kompleks dan berpihak pada prinsip keberlanjutan. Oleh karena itu, sangat penting untuk membekali siswa dengan kompetensi berpikir sistem sebagai bekal dalam menghadapi permasalahan lingkungan. Kompetensi berpikir sistem mencakup kemampuan mengenali dan memahami komponen serta hubungan timbal balik antarkomponen dalam suatu sistem yang kompleks, serta kemampuan menghadapi ketidakpastian dari tindakan yang diambil. Namun masih sedikit penelitian yang membahas tentang bagaimana siswa sekolah menengah mengonseptualisasikan dan menerapkan pemikiran sistem dalam konteks lingkungan dunia nyata. Penelitian ini bertujuan untuk mengetahui tingkatan kompetensi berpikir sistem siswa SMA. Sampel penelitian terdiri dari 133 siswa kelas X pada tahun ajaran 2024–2025 di Aceh Timur. Teknik pengumpulan data menggunakan instrumen tes berupa 8 soal esai yang disusun berdasarkan kerangka kompetensi berpikir sistem dari UNESCO. Analisi Data dengan uji Pearson dan Nilai Cronbach Alpha 0,79 (Sedang) dan Statistik Deskriptif untuk tingkatan berpikir sistem. Hasil penelitian menunjukkan bahwa sebagian besar siswa berada pada tingkat kompetensi kurang (Level 1) dan cukup (Level 2). Belum ditemukan siswa yang mencapai tingkat kompetensi baik (Level 3 dan 4). Penelitian ini memberikan gambaran awal mengenai kompetensi berpikir sistem siswa SMA serta menegaskan urgensi perlunya pengembangan intervensi pembelajaran yang tepat guna meningkatkan kemampuan berpikir sistem dalam rangka mendukung partisipasi aktif siswa terhadap pembangunan berkelanjutan. Oleh karena itu, hasil ini memberikan standar untuk merancang intervensi yang terarah dan bertujuan memajukan pendidikan berkelanjutan.